2020
DOI: 10.1098/rsta.2020.0178
|View full text |Cite
|
Sign up to set email alerts
|

A new method for detecting solar atmospheric gravity waves

Abstract: Internal gravity waves have been observed in the Earth’s atmosphere and oceans, on Mars and Jupiter, and in the Sun’s atmosphere. Despite ample evidence for the existence of propagating gravity waves in the Sun’s atmosphere, we still do not have a full understanding of their characteristics and overall role for the dynamics and energetics of the solar atmosphere. Here, we present a new approach to study the propagation of gravity waves in the solar atmosphere. It is based on calculating the three-dimensional c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In local helioseismology, this quantity is normally computed from the inverse Fourier transform of the velocity power spectrum. For multiheight Doppler observations, one could obtain this quantity by computing the inverse transform of the cross-spectrum, which Calchetti et al (2021) demonstrated. A 2D slice through this quantity at a constant time produces a ring shape in the x-and ydirections.…”
Section: Time-distance Analysis Of Agwsmentioning
confidence: 98%
See 2 more Smart Citations
“…In local helioseismology, this quantity is normally computed from the inverse Fourier transform of the velocity power spectrum. For multiheight Doppler observations, one could obtain this quantity by computing the inverse transform of the cross-spectrum, which Calchetti et al (2021) demonstrated. A 2D slice through this quantity at a constant time produces a ring shape in the x-and ydirections.…”
Section: Time-distance Analysis Of Agwsmentioning
confidence: 98%
“…To explore these features, we consider a very simple simulation of propagating AGWs comparable to that of Calchetti et al (2021). We use a numerical 2D box set in the x-z plane extending about 25 Mm wide and a few Mm in height to propagate perturbations due to AGW packets.…”
Section: Time-distance Analysis Of Agwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of the gravity waves in the solar atmosphere has, however, been a challenging task. Using a three-dimensional cross-correlation technique involving time series of vertical velocities measured at different atmospheric heights, Calchetti et al [35] propose a new approach to directly identify and characterize gravity waves in the lower solar atmosphere. The authors further validate their method using an observational dataset as well as a simple numerical model.…”
Section: Publications In the Special Issuementioning
confidence: 99%
“…Detection of the gravity waves in the solar atmosphere has, however, been a challenging task. Using a three dimensional cross-correlation technique involving time series of vertical velocities measured at different atmospheric heights, Calchetti et al [35] propose a new approach to directly identify and characterise gravity waves in the lower solar atmosphere. The authors further validate their method using an observational dataset as well as a simple numerical model.…”
Section: (C) Gravity Wavesmentioning
confidence: 99%